2020
DOI: 10.1016/j.hrthm.2020.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term results of bipolar radiofrequency catheter ablation of refractory ventricular arrhythmias of deep intramural origin

Abstract: BACKGROUND Successful bipolar radiofrequency catheter ablation (RFCA) of refractory ventricular arrhythmias (VAs) has been reported. However, the efficacy, safety, and long-term outcomes of bipolar RFCA of VAs are not fully determined.OBJECTIVE The purpose of this study was to evaluate the effectiveness and safety of bipolar RFCA in treating refractory VAs during long-term follow-up.METHODS Eighteen patients who underwent bipolar RFCA for ventricular tachycardia (VT) at 7 institutions were retrospectively inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Because of the high current density between the two ablation catheters, BIP ablation can create deeper lesions as compared with UNIP ablation, and this has been proven both by experimental and clinical studies 3–5 . Indeed, several clinical studies reported that UNIP ablation refractory arrhythmias originating from deep inside the myocardium were successfully ablated following BIP ablation with excellent acute and long‐term outcomes 10,11 . Therefore, BIP ablation is considered an important therapeutic option in some patients but parameters for safely performing the BIP ablation have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the high current density between the two ablation catheters, BIP ablation can create deeper lesions as compared with UNIP ablation, and this has been proven both by experimental and clinical studies 3–5 . Indeed, several clinical studies reported that UNIP ablation refractory arrhythmias originating from deep inside the myocardium were successfully ablated following BIP ablation with excellent acute and long‐term outcomes 10,11 . Therefore, BIP ablation is considered an important therapeutic option in some patients but parameters for safely performing the BIP ablation have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, in several studies, 9,15 these indexes were reported to be insufficient to prevent the occurrence of steam‐pop. Although steam‐pop‐related complications were rare in the clinical studies, 10,11 caution is required because experimental studies using a relatively high energy delivery showed a high incidence of steam‐pop during BIP ablation 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible reason is a more common midmyocardial or epimyocardial distribution of the often partly patchy substrate in nonischemic cardiomyopathy that might not be detected with an endocardial mapping approach 23,24 . A substrate of that kind might be more accessible through an epicardial or in some cases bipolar ablation approach 25 . Furthermore, depiction of the myocardial scar by magnetic resonance imaging or computed tomography might be helpful to identify the optimal ablation strategy 26 …”
Section: Discussionmentioning
confidence: 99%